Impact of falling remittances amid COVID-19 on Yemen’s war-torn economy - Elsabbagh, Dalia; Kurdi, Sikandra; Wiebelt, Manfred (International Food Policy Research Institute, 2022)
Even before the COVID-19 pandemic battered economies across the world, Yemen had already experienced a half decade of civil war, resulting in a loss of approximately 45 percent of its real GDP by the end of 2019, according to the Yemeni Ministry of Planning. As the conflict continued, remittances from Yemenis working outside the country kept many households afloat and became an increasingly important source of income, estimated at $3.77 billion in 2019 — around 13 percent of GDP.